2020
DOI: 10.1055/s-0040-1701213
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method of Cervicoplasty Using Autologous Peritoneum for Cervicovaginal Atresia

Abstract: Cervicovaginal atresia with a functional uterus is rare. There are no established surgical methods to treat this condition, and only a few reports have been published on surgical techniques. Furthermore, postoperative complications, such as restenosis, often require reoperation. A 19-year-old woman was pointed out cervical hypoplasia and referred to our hospital for further examination and treatment. A pelvic examination revealed that the vagina had a slight recession with a blind end. Transrectal ultrasound a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…As for the treatment of congenital cervical malformations, conservative management has been gradually performed recently, as it can relieve symptoms, establish the normal sexual function, and preserve the uterus for future fertility [4] . A great variety of materials and techniques have been used to reconstruct the vagina and cervix [6,[12][13][14][15] . Some studies have reported using the SIS graft to reconstruct the vagina and cervix [6,7,16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the treatment of congenital cervical malformations, conservative management has been gradually performed recently, as it can relieve symptoms, establish the normal sexual function, and preserve the uterus for future fertility [4] . A great variety of materials and techniques have been used to reconstruct the vagina and cervix [6,[12][13][14][15] . Some studies have reported using the SIS graft to reconstruct the vagina and cervix [6,7,16] .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the presence of vaginal agenesis, all patients underwent vaginoplasty concomitantly with no complications in this study. Fujino et al reported a two-step technique in which a radical surgery was performed ten months later after vaginoplasty [15] . It was thought to be safer but may increase the risk of pain or endometriosis.…”
Section: The Cervicovaginal Anastomosis Can Be Performed By Minimally Invasive Surgerymentioning
confidence: 99%
“…Each of these steps is crucial for the unremarkable development of the female internal genitalia, and disruption at any point can cause different types of genital developmental disorders, including cervical agenesis or aplasia [ 1 , 2 , 3 ]. In general, Müllerian duct anomalies are described in 4–7% of the female population, although cases of cervical agenesis or aplasia (with or without a vagina) but with a functional uterus are rare [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, gynecological specialists seek not only to reduce morbidity but also to conserve the possibility of reproductive capacity. Therefore, there have been some reports describing surgical management [ 6 , 10 , 11 ]. In this article, we present different surgical approaches to uterus-conserving surgical therapy for different Mullerian anomalies performed at the Department for Women’s Health of the University of Tuebingen, Germany, between 2017 and 2022.…”
Section: Introductionmentioning
confidence: 99%